Head-to-Tail and Head-to-Head Molecular Chains of Poly(p-anisidine): Combined Experimental and Theoretical Evaluation - Oliveira, Lilian Rodrigues de (2022)
Poly(p–anisidine) (PPA) is a polyaniline presenting a methoxy (–OCH3) group at the para position of the phenyl ring. Considering the important role of conjugated polymers in novel technological applications, a systematic, combined experimental and theoretical investigation had been performed to get more insight into the crystallization process of PPA. Conventional oxidative polymerization of p–anisidine monomer was based on a Central Composite Rotational Design (CCRD). The effect of the concentration of the monomer, ammonium persulfate (APS) and HCl on the percentage of crystallinity was considered. Several experimental techniques such as X-Ray diffraction (XRD), Scanning Electron Microscopy (SEM), Multifractal Analysis, Nuclear Magnetic Resonance (13C NMR), Fourier-transform Infrared Spectroscopy (FTIR), Complex Impedance Spectroscopy analysis besides Density Functional Theory (DFT) were employed to perform a systematic investigation of PPA. The experimental treatments resulted in different crystal structures with the percentage of crystallinity ranging from (29.2 ± 0.6) % (PPA1HT) to (55.1 ± 0.2) % (PPA16HT-HH). The XRD patterns of PPA1HT and PPA16HT-HH were clearly correlated, but more defined in PPA1HT. A broad hallo in the PPA16HT-HH pattern from 2θ = 10.0° – 30.0° suggested reduced crystallinity. Basically, two types of morphology were observed in both samples: needles and globular particles. SEM images suggested that the needles morphology might be related to the crystalline contribution. Multifractal analysis showed that the PPA surface became more irregular and complex when the crystallinity was reduced. The proposed molecular structures of PPA were supported by the high-resolution 13C NMR results, allowing to access the percentage of head–to–tail (HT) and head–to–head (HH) molecular structures: PPA1HT was fully (100%) constituted of HT polymer chains (PPAHT), while PPA16 was formed predominantly by HT molecular structure [(62.0 ± 0.5) %; PPAHT-HH). Comparing calculated and experimental FTIR spectra, the most pronounced changes were observed in ν(C–H), ν(N–H), ν(C–O) and ν(C–N–C) due to the influence of counter ions, as well as by the different mechanisms of polymerization. Finally, a significant difference in electrical conductivity values was observed in the range of 1.00 x 10-9 S.cm-1 and 3.90 x 10-14 S.cm-1, respectively, for PPA1HT and PPA16HT-HH.